School principals’ perception of the progressive discipline of educators in Johannesburg North District schools - Jaffer, Moefiedah (My University, 2012)
It is the task of school principals to ensure that educators uphold the highest standards of conduct and in the process hundreds of disciplinary hearings for educators had been conducted over the past decade for different allegations of misconduct. The primary purpose of this research was to explore school principals’ perception of progressive disciplinary procedures for educators. The study adopted a qualitative approach that used inductive data analysis techniques. Some findings were that most principals do not apply progressive discipline consistently and were ambiguous about the effect of the process on educator conduct. Many were threatened and intimidated when using the procedure. This was aggravated by delays in completing the formal process. Principals prefer the least adversarial approach in progressive discipline practice. They spend much time monitoring to prevent or avoid the disciplinary procedure and deviate from the procedure to cope with their anxieties and concern for relations with staff.
MM thesis - P&DM
Keywords: School discipline; Discipline at schools; Disciplining of educators